Association between neuropeptide Y gene polymorphism and antipsychotics effect - Zhang, Qian; Wan, Yajie; Du, Xinzhe; Gao, Yao; Wang, Xiao; Wu, Kewen; Zheng, Xiaohu; Wang, Yu; Zhao, Cheng; Li, Li; Guo, Xianju; Li, Xinrong; et al. (Frontiers in Psychiatry, 2022)
Objective:The pathogenesis of schizophrenia is associated with neuropeptide Y (NPY) gene polymorphism to explore the relationship between rs16141、rs16145 and rs5573 polymorphisms in the NPY gene and antipsychotics response in the Chinese population. Methods: The unrelated 228 Chinese Han patients with schizophrenia were enrolled in the present study. Genotypisation within NPY gene was performed using the KASP genotyping assays. Before treatment and on the weekends of the 2nd, 4th, and 8th weeks after treatment, the medication status of the patients was recorded and the positive and negative syndrome scale (PANSS) was used to evaluate the clinical effect. A reduction in total PANSS scores ≥ 50% were classified as good responders, while others were poor responders.We evaluated the association between NPY gene and antipsychotic efficacy by comparing allele and genotype distribution, correlation analysis, linkage imbalance, and five genetic models between the two groups. Results: No significant associations were found in the rs16141, rs16145 and rs5573 of NPY and antipsychotic treatment response (all p > 0.05). There was no significant relationship between the three SNPs polymorphisms in the NPY gene and the changes of positive, negative and general psychopathology subscales scores at each stage (all p > 0.05). The distribution of genotype and allele frequencies of locus rs16141 was not statistically difference between good responders and poor responders (genotype: χ2 =4.088，p=0.043，p-correction =0.129; allele: χ2 = 4.088, p = 0.027, p-correction =0.081). The allele distribution of rs5573 was significantly different between groups, yet the difference was disappeared after correcting (χ2 = 4.136, p = 0.042, p-correction =0.126 ). The distribution frequencies of TA/TG and GG haplotypes constituted by rs16141 and rs5573 showed no statistical difference between the two groups (p > 0.05). In recessive inheritance mode, rs5573 was found to be associated with antipsychotic drug response (G/G vs. A/A +A/G: p = 0.028, AIC = 197.2, BIC = 210.9). Conclusions：This study didn’t found association between polymorphisms in the NPY gene locus (rs16141, rs16145 and rs5573) and the response to antipsychotics after Bonferroni correction. The polymorphism of NPY gene and the efficacy of antipsychotic drugs in patients with schizophrenia need further study.